Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Materi Statistika Kelas VIII Berdasarkan Langkah Penyelesaian Polya - Rora Artanti; Septi Nur Hayati; Khoirunnisa, Fita (Papanda, 2022)
This study aims to describe the types of errors, percentages, and factors causing errors made by class VIII students of SMP Negeri 4 Pekalongan in solving statistical problems based on Polya's completion steps. Solving story problems based on Polya's completion steps consists of four stages, namely understanding the problem, making plans, implementing plans, and re-examining the solutions obtained. This research is a type of descriptive research with a qualitative approach. The method used is the test method. The subjects of this study were students of class VIII SMP Negeri 4 Pekalongan, totaling 26 students. The results of the research conducted showed that the most frequent mistakes made by class VIII students of SMP Negeri 4 Pekalongan were errors in completing plans with a percentage of 34.62%, then errors in planning plans by 29.92%, errors in re-checking the completion. obtained by 19.23%. , and the fewest errors made by students were errors in understanding the questions with a percentage of 7.69%.